Strategic Choices for Balancing Intimacy and Professionalism: Content Analysis of Chinese Podcasts on Himalaya - Xu, Jinghong (2025)
By analyzing 120 episodes from 12 podcast accounts, representing central, provincial, commercial, and individual Chinese news outlets on the Himalaya platform, this study examines the strategies employed by news publishers to balance intimacy and professionalism. Our findings show that while all media types prioritize professionalism, their strategies for cultivating intimacy differ significantly. Compared to commercial and provincial media, central media achieved the best balance between intimacy and professionalism. Individual media demonstrated the highest intimacy scores, whereas central media excelled in professionalism. This study enhances our understanding of how institutional backgrounds shape strategies in audio journalism. It offers insights into balancing intimacy with professional standards in the podcast medium.